2011
DOI: 10.1111/j.2042-3306.2010.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastric ulcer syndrome in high-level endurance horses

Abstract: This prevalence of EGUS in high-level endurance horses is comparable to the prevalence established in racing horses. The equine veterinarians may take into consideration EGUS as a potential cause of poor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 25 publications
5
83
2
13
Order By: Relevance
“…Standardbred racehorses have a similar overall ESGD prevalence of 44% that rises up to 87% in training,8, 9, 10 while 17–58% show/sport horses and 37–59% of pleasure horses are affected 11, 12, 13, 14, 15. Endurance horses have an ESGD prevalence of 48% during the out of competition period that rises to 66–93% during the competitive period, with lesions most prevalent in elite horses 16, 17. Horses that are rarely competed and predominantly used in their home environment have the lowest ESGD prevalence of 11% 18…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Standardbred racehorses have a similar overall ESGD prevalence of 44% that rises up to 87% in training,8, 9, 10 while 17–58% show/sport horses and 37–59% of pleasure horses are affected 11, 12, 13, 14, 15. Endurance horses have an ESGD prevalence of 48% during the out of competition period that rises to 66–93% during the competitive period, with lesions most prevalent in elite horses 16, 17. Horses that are rarely competed and predominantly used in their home environment have the lowest ESGD prevalence of 11% 18…”
Section: Prevalencementioning
confidence: 99%
“…Australian Thoroughbred racehorses have reported prevalences of between 47%6 and 65% 19. In endurance horses, the prevalence is 16% outside of the competition period and 27–33% while competing 16, 17. A retrospective study in the United Kingdom found EGGD in 54% of 191 leisure horses and in 64% of 493 sport horses 20.…”
Section: Prevalencementioning
confidence: 99%
“…The animals were evaluated in two periods of the year, during the resting season and then during the competition season. The authors reported an incidence of 43% during the resting period and 93% during the competitions (TAMZALI et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…EGUS also affects horses involved in others disciplines such as endurance (Tamzali et al, 2011), show horses (White et al, 2007) and horses not involved in competition, such as broodmares (Le Jeune et al, 2009). EGUS is associated with several risk factors, i.e., stress (Malmkvist et al, 2012), intense training and competition (Roy et al, 2005;Jonsson and Egenvall, 2006) and diet (Nadeau et al, 2003;Andrews et al, 2008).…”
Section: Introductionmentioning
confidence: 99%